ANIMAL WELFARE AS ONE OF THE CRITERION DETERMINING POLISH CONSUMERS’ DECISIONS REGARDING THEIR PURCHASE OF MEAT - Gołębiewska, Barbara; Gębska, Monika; Stefańczyk, Joanna (Acta Scientiarum Polonorum. Oeconomia, 2018)
The aim of this study was to determine factors influencing consumer decisions on the purchase of meat and find out how important in making the decisions is the criterion of animal welfare. The study was based on reports and other publications of the European Commission, literature review, as well as field research carried out among consumers, using an interview questionnaire (the PAPI method). The purpose of the research was to analyse diversity of customer buying habits, depending on such variables as their age, education, place of residence (urban or rural area) and the level of income. The results of the χ2 test prove that there are correlations between the education, place of residence and income of the respondents and their decisions to purchase meat from farms maintaining animal welfare. No correlations were found between the age of the respondents and their decisions to purchase meat from farms maintaining animal welfare. The findings also prove that less than 50% of the society of Poland has encountered the concept of animal welfare. The key criteria for decisions on the purchase of meat and meat products were the price and easy preparation.